2021
DOI: 10.1055/s-0041-1740135
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Functional Outcome of the Linked Semiconstrained Distal Radioulnar Joint Prosthesis

Abstract: Background A painful unstable distal radioulnar joint (DRUJ) can seriously compromise hand and wrist function. The semiconstrained prosthesis was developed to restore DRUJ function. To date, most outcome reports are coauthored by the designer. Questions Does independent reporting confirm the promising results of the semiconstrained DRUJ prosthesis? Are complication and failure rates acceptable? Patients and Methods We evaluated patients with the semiconstrained DRUJ implant and a minimum fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…Between 1997 and 2018, the DRUJ Aptis TM was implanted in more than 3600 patients worldwide (Lans et al., 2019), with patient satisfaction of 98% (Calcagni and Giesen, 2017; Moulton and Giddins, 2017). Although many of these results have been reported with the implant designer as author or co-author (Galvis et al., 2014; Lans et al., 2019; Laurentin-Pérez et al., 2008; Rampazzo et al., 2015; Savvidou et al., 2013; Scheker, 2008; Scheker and Martineau, 2013), other studies published by independent authors agree with the increasing use and the effectiveness of the device (Bellevue et al., 2018; Brannan et al., 2022; DeGeorge et al., 2019; Degreef and De Smet, 2013; Kachooei et al., 2014; Lambrecht et al., 2022; Lees, 2023; Martínez Villén et al., 2014; Reissner et al., 2016; Warlop et al., 2022). However, a systematic review by Moulton and Giddins (2017) of the total DRUJ prosthesis, found only 12 full-text studies with adequate methodological quality.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Between 1997 and 2018, the DRUJ Aptis TM was implanted in more than 3600 patients worldwide (Lans et al., 2019), with patient satisfaction of 98% (Calcagni and Giesen, 2017; Moulton and Giddins, 2017). Although many of these results have been reported with the implant designer as author or co-author (Galvis et al., 2014; Lans et al., 2019; Laurentin-Pérez et al., 2008; Rampazzo et al., 2015; Savvidou et al., 2013; Scheker, 2008; Scheker and Martineau, 2013), other studies published by independent authors agree with the increasing use and the effectiveness of the device (Bellevue et al., 2018; Brannan et al., 2022; DeGeorge et al., 2019; Degreef and De Smet, 2013; Kachooei et al., 2014; Lambrecht et al., 2022; Lees, 2023; Martínez Villén et al., 2014; Reissner et al., 2016; Warlop et al., 2022). However, a systematic review by Moulton and Giddins (2017) of the total DRUJ prosthesis, found only 12 full-text studies with adequate methodological quality.…”
Section: Discussionmentioning
confidence: 98%
“…Warlop et al. (2022) reported discrete radiographic periprosthetic osteolysis in three prostheses out of a total of 42 (7%) with a mean implant follow-up of 3.8 years; Brannan et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations